Cryptocurrency and cybercrime – the need to strengthen the legal framework - Puniran, Mohd Noor Ikram; Zul Kepli, Mohd Yazid (Universiti Malaysia Terengganu, 2018)
This paper explores the legal and regulatory challenges for digital and virtual currency in Malaysia, with special focus on cryptocurrency like Bitcoin. The emphasis is on cybercrime and consumer protection. Since very few countries have adequate legislation to regulate virtual currency, it has been widely exploited by scammers and syndicates for money laundering, hacking, terrorism financing, fraud, and other illegal purposes. This paper is mostly library based with newspaper reports, established books and articles being the main references. This paper also benefited from interviews with experts. This paper stresses that it is crucial to have a clear legal standard for the licensing, control and management of cryptocurrency exchanger in particular and cryptocurrency in general. The legal standard can be achieved by adopting the best practices from other countries including Japan, United States, and South Korea. The article also proposes ways to properly adapt cryptocurrency safely into our daily life and how we should take advantage of it.